Aducktive / Nurul Aida Ramli - Ramli, Nurul Aida (2021)
The crunchy is a sole proprietorship business that sells products in online. This business owned by Nurul Aida Binti Ramli. In 2021, the owner of Aducktive by Aidaramlii decided it was high time for her to create her own business services after several years of observing business. The owner chose to build this kind of company as it is suitable for building a small business but profitable. Aducktive Spicy Salted Egg Cornflakes is one of the wholesale bakeries that also known as pure play business because selling product through online platform. The main objective of this business company is to produce healthy snacks for customers without monosodium glutamate (MSG). The product also only used natural ingredients and fully homemade also halal. The targets customers are come from all level of ages (but not suitable for babies) who can consumed the product from Aducktive Salted Egg Cornflakes. We also offered affordable prices and cheaper prices in the market. This is because; everyone can afford to buy and tastes the addictive salted egg cornflakes. Moreover, we used online platform fully in order to promote, marketing and sales of products. This has helped the company a lot in saving many costs involved and can reach widen target customers.